30-day readmission prevention program in heart failure patients (RAP-HF) in a community hospital: creating a task force to improve performance in achieving CMS target goals. Issue 5 (2nd September 2020) - Macchio, Phyllis; Farrell, Lorraine; Kumar, Vikas; Illyas, Wajiah; Barnes, Martin; Patel, Himani; Silverman, Andrew L.; Hong Le, Thuy; Siddique, Haseeb; Raminfard, Albert; Tofano, Michael; Sokol, Jacob; et al.
ABSTRACT: In 2012, Centers for Medicare and Medicaid Services (CMS) announced it would penalize any hospitals that had 30-day readmission rates for heart failure (HF) patients above 20%. Mather Hospital Northwell Health, a community teaching hospital, organized a proactive task force to meet these goals. We describe our hospital-wide Readmission Prevention in Heart Failure (RAP-HF) project. We focused on the following interventions: early identification of patients at risk for readmission, discipline-specific mitigation planning by the interdisciplinary rounding team, enhanced medication education for heart failure patients, education of family/caregivers on medication and heart failure symptoms, facilitation in scheduling of post-discharge follow up visits and hard-wired communication between hospital and post-discharge care providers. We saw a 25.53% decrease in 30-day readmission rates.